The poetic of the prose text in the book Nahj al-Balagha (Imaginary creativity in describing the creation of the peacock) - Kahdim Sahal, Dailam (International Journal of Psychosocial Rehabilitation, 2020)
Zoology is like another science of nature that did not originate in a specific period or develop scientific changes in a specific civilization period. That is, it is mainly related to human life and their livelihood requirements since the inception of Homo sapiens in ancient times. The animals had been known in Mesopotamia since ancient times, what is known as the Pre-Historic periods. Since man knew types of wild animals and then domesticated certain species of them for their meat, skins, and bones, as well as for use in agriculture work, traction, transportation, and cargo transport. This research focuses on the study of animals in Mesopotamia literature, whether it is poetry or prose, as the animal was mentioned in several literary texts, including the texts of literary debates, stories, navigation, spells, and others, and most of them had older origins. This was due to the interest of the Mesopotamian kings and rulers in their cultural heritage. Including the heritage of ancient literary. In addition, the research will deal with animals in the Arab Islamic literature and their implications. Several literary texts, poetic and prose, mention a number of animals of various kinds. In view of the broad subject matter, we focused on one of the well-known birds, which is the peacock, which is known to be one of the most amazing, beautiful, and best-created birds. It is one of the most beautiful ornamental birds in the world. The study will deal with the peacock with what was mentioned in the sermon of Imam Ali in Nahj al-Balaghah, describing it, its colors, and its typography.